Positive youth development through an outdoor physical activity programme: evidence from a four-year evaluation - Kathleen Armour; Rachel Sandford (2013)
In 2006, Sandford, Armour and Warmington undertook a comprehensive review of the literature on the role of physical activity/sport and physical education in promoting positive development for disaffected youth. This paper revisits the findings of the literature review in light of data from a four-year evaluation of one corporate-sponsored physical activity intervention in the UK. Literature on the role of physical activity/sport in positive youth development (PYD) is summarised and updated from the original review. Impact data were collected on approximately 600 pupils (310 boys and 285 girls) and showed that there were some positive benefits for the majority of participants and that those pupils who participated for longer showed more sustained improvements. It is argued, however, that physical activity settings are no panacea, and that complex understandings of learning and skill “transfer” from such programmes are required if sponsors and designers are to maximise the potential of sport/physical activity for positive youth development.